2008
DOI: 10.1080/16066350802100822
|View full text |Cite
|
Sign up to set email alerts
|

Rumination in problem drinkers

Abstract: The present study explored the role of the general tendency to ruminate as a predictor of problem drinking (alcohol abuse) in clinical and community samples. A sample of 36 patients with a diagnosis of problem drinking and 37 social drinkers from the general population were compared on the following measures: Beck Depression Inventory (BDI), Ruminative Responses Scale (RRS) and Quantity Frequency Scale (QFS). Mann-Whitney U-tests, and logistic and hierarchical regression analyses were performed on the data. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 33 publications
5
50
1
Order By: Relevance
“…On similar lines desire thinking has been found to discriminate between problematic and nonproblematic Internet users (Spada, Caselli, Slaifer, Nikčević & Sassaroli, 2013). Research has also demonstrated that rumination is higher for problem drinkers compared to social drinkers (Caselli, Bortolai, Leoni, Rovetto, & Spada, 2008), that it prospectively predicts alcohol use in community and clinical samples (Caselli, Ferretti, Leoni, Rebecchi, Rovetto & Spada, 2010) and that it brings to increases in craving in experimental conditions …”
Section: Extended Thinkingmentioning
confidence: 90%
“…On similar lines desire thinking has been found to discriminate between problematic and nonproblematic Internet users (Spada, Caselli, Slaifer, Nikčević & Sassaroli, 2013). Research has also demonstrated that rumination is higher for problem drinkers compared to social drinkers (Caselli, Bortolai, Leoni, Rovetto, & Spada, 2008), that it prospectively predicts alcohol use in community and clinical samples (Caselli, Ferretti, Leoni, Rebecchi, Rovetto & Spada, 2010) and that it brings to increases in craving in experimental conditions …”
Section: Extended Thinkingmentioning
confidence: 90%
“…Therefore it is plausible, yet remains untested, that females may experience greater stress and cue-induced craving as a function of elevations in rumination or desire thinking. Interestingly, the aforementioned associations between rumination and drinking status hold even after controlling for co-occurring depressive symptoms (Caselli et al, 2008;Caselli et al, 2010). According to this line of research, individuals with such preservative cognitive styles may hold stressful information in mind longer and perhaps even elaborate on its content, thus leading to greater increases in alcohol craving.…”
Section: Introductionmentioning
confidence: 98%
“…In a study of cue reactivity, it was found that women were more reactive to alcohol cues than men when in a negative mood state (Rubonis, Colby, Monti, Rohsenow et al, 1994). While the cognitive mechanisms by which individuals may be more vulnerable to stress and/or cueinduced craving remain opaque, recent studies have found that rumination (Caselli, Bortolai, Leoni, Rovetto, & Spada, 2008;Caselli et al, 2010) and desire thinking (Caselli & Spada, 2011) predict drinking status broadly. Rumination, defined as a passive focus on one's symptoms of distress and possible causes and consequences of those symptoms, has been found to be elevated among females (Nolen-Hoeksema & Jackson, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of relationship between rumination and alcohol consequences was unexpected, given the relationship between rumination and PBS that was found. Ciesla et al (2011) found a similar null relationship in a college student sample when examining the association between depressive rumination and alcohol consumption and suggested that the lack of association, found to be significant in other studies (Caselli et al, 2008(Caselli et al, , 2010NolenHoeksema & Harrell, 2002), may not be significant in populations with subclinical levels of disordered alcohol use and/or depression. Instead, populations with subclinical levels of alcohol abuse and/or depression may be consuming alcohol not due to their ruminative thoughts but for positive alcohol expectancies.…”
Section: Chapter IV Discussionmentioning
confidence: 91%
“…Nolen-Hoeksema and Harrell (2002) found that rumination was associated cross-sectionally with alcohol use for men and women, and predicted alcohol problems up to 12 months later for women. Moreover, rumination predicted alcohol consumption in adults with alcohol abuse (average age = 47.2 years, SD = 9.5 years; Caselli et al, 2010) and in a sample of both adults with and without an alcohol problem diagnosis (average age = 47.8 years, SD = 8.8 years; Caselli, Bortalai, Leoni, Rovetto, & Spada, 2008). However, only a few studies researched the role of rumination in college students.…”
Section: Rumination Alcohol and Pbsmentioning
confidence: 99%